DEVELOPMENT AND EVALUATION OF NANOEMULSION FORMULATIONS FOR IMPROVED ORAL DELIVERY OF CARVEDILOL - Chidi, Edenta; N, Ezeaku Ikenna; Zainab, Adamu; John, Dingwoke Francis (Universal Journal of Pharmaceutical Research, 2017)
Objective: The aim of the present investigation was to develop, optimize and evaluate nanoemulsion system of carvedilol to improve its solubility, and oral bioavailability. Carvedilol is a non-selective beta blocker used in the treatment of mild to moderate congestive heart failure and mild to moderate essential hypertension. It has both poor water solubility (0.583 mg/L) and oral bioavailability (23%) because of significant first-pass hepatic metabolism. Methods: Based on solubility testing, clove oil was used as oil, tween 20 was used as surfactants and PEG 400 was used as cosurfactants in construction of phase diagrams. Carvedilol nanoemulsions were prepared by aqueous phase titration method. Out of twelve formulations, eight thermodynamically stable formulations were selected for preparation of carvedilol loaded nanoemulsions and these nanoemulsions were subjected for characterization i.e. particle size, viscosity, polydispersity, zeta potential. A 12 hrs in-vitro release release study was performed on selected nanoemulsion formulations of carvedilol. Results: The results of viscosity of carvedilol nanoemulsions were found to be in range (60.42 –134.63 m Pa.sec.). The results of pH measurement for formulations explain that the pH values of drug free nanoemulsions were slightly acidic. All formulations have PDI value less than (1.0). Conclusion: Study concludes, nanoemulsion formulation of batch NEC4 (Smix ratio 1:3) was found to be optimum formulation. Peer Review History: Received 6 December 2016; Revised 5 January 2017; Accepted 12 February, Available online 15 March 2017 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Dr. Maha Khalifa Ahmed Khalifa , Al-Azhar Universit - Cairo, Egypt, mahakhalifa.ahmed@hotmail.com